Peran Literasi Keuangan, Financial Self-Efficacy dan Fintech Payment Terhadap Manajemen Keuangan Pribadi Mahasiswa MKS UIN SATU Tulungagung - Sofa, Indah Ainus; Riyadi, Berlian Gustina; Ningtyas, Surur Fathma; Yudiantoro, Deny (FEB Universitas Maritim Semarang, 2024)
This research explores the influence of financial literacy, self-confidence in managing personal finances, and the use of fintech payments on the personal financial management of Sharia Financial Management students at UIN Sayyid Ali Rahmatullah Tulungagung. This research is motivated by students' lack of understanding regarding personal financial management, which has the potential to affect their readiness to face financial challenges in the future. Through good financial literacy and self-confidence in managing finances, students are expected to be able to manage their finances more wisely. On the other hand, the use of fintech payments is also thought to have an influence on students' financial management behavior. This research uses a quantitative approach with associative methods and purposive sampling techniques, involving 86 students from the class of 2020-2022. Data was collected via questionnaire, then analyzed using multiple linear regression via SPSS-26. The research results show that financial literacy, financial self-efficacy, and payment fintech together have a positive and significant influence on personal financial management, financial literacy has a positive and significant influence, financial self-efficacy has a positive and significant influence, and payment fintech also has an influence positive and significant on students' personal financial management.